TINGKAT KUALITAS KEPELATIHAN PELATIH AKADEMISI DITINJAU DARI KONDISI FISIK DAN TEKNIK DASAR PERMAINAN SEPAKBOLA ANAK ASUHNYA - Prianto, David Agus (Journal of Sport and Exercise Science, 2020)
The purpose of this study was to determine the ability of academic coaches to train physical conditions and basic techniques of early childhood football. The target of this research is SSB coaches with academic backgrounds from football school clubs (SSB) in Surabaya, Sidoarjo and Gresik, each taken as 2 Coaches. As for the research subjects were foster children aged 12-14 years with a total of 30 children. This research used quantitative descriptive, while the method used in this study was a survey, namely data collection using only tests and measurements by doing a physical condition test which includes: endurance , speed, strength, and agility. As well as basic football technical tests which include: pass down, pass up, shooting, throw in, heading, dribbling, and juggling. Conclusion: (1) Based on table two it can be seen that the quality category of the players' physical condition from the academic coaches is: 15 players (12.50%) are in the very good category, 27 players (22.50%) are in the good category, as many as 45 players (37.50%) were in the moderate category, 23 players (19.17%) were in the low category, and as many as 10 players (8.33%) were in the very poor category. (2) Based on the table above, it is known that the basic technical quality categories of players from academic coaches are: 66 players (55.00%) are in the very good category, 52 players (43.33%) are in the good category, and as many as 2 players. (1.67%) is in the medium category.